FRI0276 Ultrasonography as Useful Tool to Identify Rheumatoid Arthritis Patients in Clinical Remission for Tapering or Withdrawal TNFA Blockers without Disease Relapse. (10th June 2014) - Alivernini, S.; Peluso, G.; Correra, M.; Fedele, A.L.; Gremese, E.; Ferraccioli, G.
Abstract : Background: Ultrasonography (US) has superior sensitivity in detecting the presence of synovial hypertrophy (SH) and its activity by Power Doppler (PD) in Rheumatoid Arthritis (RA). The relapse rate is nearly 50% after biologic treatment withdrawal due to disease clinical remission. Objectives: The aims of the study were to assess the US SH rate in a cohort of RA patients in clinical remission who tapered first and stopped thereafter anti-TNFα treatment and to evaluate if US characteristic (SH thickening rate) could predict any clinical relapse. Methods: 49 RA patients in clinical remission (DAS<1, 6) underwent baseline US evaluation (dorsal and volar view scanning of II-III MCP and II-III PIP bilaterally, wrists, knees and II-V MTP bilaterally). At baseline, RA patients were stratified into 2 subgroups as SH+/PD- and SH+/PD+, based on US characteristics. SH+/PD- patients tapered anti-TNFα treatment (Adalimumab 40 mg/monthly or Etanercept 50 mg/2 weeks) for 3 months. After biologic tapering, RA patients who were still PD-, stopped biologic and were followed for at least 3 months, maintaining only DMARDs. Treatment modifications were not allowed during the study. Relapse rate was recorded for each patient (DDAS >1, 2 from the DAS value at the time of last US assessment). Results: At the study entry, 7 (14, 3%) RA patients were SH+/PD+ whereas 42 (85, 7%) patients were SH+/PD- and tapered the biologic. No patients were SH-/PD-. After 3 months tapering, 13 (30, 9%) RA patients showed disease relapse. RA patients who relapsed, did not differ for anti-CCP (p=0, 85), IgA-RF (p=0, 25) and IgM-RF (p=0, 51) positivity, smoking habit (p=0, 47) and biologic type (p=0, 69) from RA patients who did not relapse. However, significantly higher SH thickening values in MCP and MTP at baseline characterized RA patients who relapsed after 3 months tapering, compared to RA patients who did not (0, 46±0, 18mm vs 0, 59±0, 14mm for MCP and 0, 36±0, 22mm vs 0, 65±0, 44mm for MTP; p=0, 05 and p=0, 01 respectively). To date, among RA patients who did not relapse after tapering, 20 (70, 0%) RA patients stopped biologic. After biologic withdrawal, 4 (20, 0%) RA patients showed disease relapse after 3, 6, 7 and 9 months respectively. All RA patients who relapsed had disease flare in the joint site, clinically involved at the time of the disease onset (80% in the MCP and 20, 0% in the knees). RA patients who relapsed did not differ for the previous demographic and immunological parameters as well as for the biologic type (16, 7% of Adalimumab treated vs 25, 0% of Etanercept treated patients have disease flare;p=0, 65). However, SH thickening rate in MTP was found higher in RA patients who relapsed after biologic stopping (0, 66±0, 42mm) than who did not (0, 38±0, 21mm;p=0, 04). Finally, all RA patients who relapsed were newly treated with the previous biologic, following the last effective therapeutic regimen. Conclusions: US based patients selection before treatment tapering and/or stopping is a useful tool to minimize disease relapse rate. Drug free remission is a possible goal in the majority RA patients without synovial tissue activity signal, with no difference between anti-TNF-α agents. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4474